Perfil sociodemográfico, nível de atividade física, dor e auto percepção de saúde de idosos em unidades de saúde de referência em município de médio porte da região centro oeste - Vilela, Daisy de Araújo (2015)
To adequately serve the elderly in health services is essential to know the socio-demographic, economic, lifestyle, people's grievances, health markers and understand differences related to gender and age groups. Objective: To describe, according to sex and age group, the demographic and socioeconomic profile; the level of physical activity; the frequency, severity, intensity and treatment of pain and self-rated health of elderly assisted in referral health facilities of a medium-sized city in the central region and western Brazil; test the relationship between physical activity level, pain and self-perception of health in the elderly. Method: This is a descriptive transversal study with a quantitative approach, with calculated sample of 300 elderly, non-randomized. Data collection was conducted from September 2013 to January 2014. The approach was uneventful in health facilities indicated as reference for treatment of the elderly. Checked the eligibility criteria, the elderly were recruited for study participation. They used four instruments to collect data: sociodemographic questionnaire, IPAC (short), BPI and health perception. Data were analyzed using descriptive statistical procedures, chi square test, Fisher's exact test, Kruskal Wallis, Mann Whitney-U, with p ≤ 0.05.Results: The predominant among the elderly assisted in the units is referred females (81.0%), mean age 67.1 years ( 5.6 years; median 66.0). The idodos showed moderate level of physical activity (74.0%). The pain had significant occurrence among participants (49.3%), with similar distribution between genders and age range. The treatment used for pain was the use of analgesics (71.0%). The elderly reported self perception of good health (23.6%) or very good (65.6%). No relationship was found between the pain and the level of physical activity and the perception of health of the elderly seen in reference health units. Conclusion: Seniors who attend referral units have characteristics that should be taken into account in the planning of care for this population activities: are predominantly young elderly, female, with a moderate level of physical activity, with mild pain, which does not interfere in daily activities, mood, sleep is controlled with painkillers; They have self-perception of good or very good health, and not show relationship between the level of physical activity, pain and health perception.